THE BAGELEN BEDS, CENTRAL JAWA - P. Lunt; H. Sugianto (Pusat Survei Geologi, 2007)
The Bagelen Beds of Cential Java are re-defined and described as a very deep marine olistostrome deposit of Early Oligocene age (about 321/2 MYBP).Â There is no indication that the clays have been tectonised and they are considered a pebbly-claystone or slump deposit rather than a tectconic melange.The benthic microfaunas are analogous to those found in open-ocean palaeobathymetries at around 3,000 metres, but it is argued that this interpretation may not be applicable to semi-restricted basins in a tectonically complex area. A shallower depth,of very roughly 1,000 to 2,000 m, is argued to be possible and that this would better fit tile epi-cratonic geological setting. The significance of a deep marine, slump-filled environment in the Early Oligocene of Central Java is discussed, and a suggestion made for the origin of the unusualÂ mud-volcano found in the Sangiran Dome.Â Keywords: Bagelen beds, Olistostrome, slum deposit benthic microfaunas, epi-cratonic